Response to a standard behavioral weight loss intervention by age of onset of obesity - Rupp, K.; Taverno Ross, S. E.; Lang, W.; Jakicic, J. M. (Obesity Science & Practice, 2016)
Background The purpose of this study was to examine weight loss, physical activity, fitness and diet changes in response to a standard behavioral weight loss intervention in adults with self-reported juvenile onset (n = 61) or adult onset (n = 116) obesity. Methods Participants (n = 177; 43.0 ± 8.6 years; body mass index [BMI] = 33.0 ± 3.4 kg m−2) engaged in an 18-month standard behavioral weight loss intervention. Participants were randomized into three different intervention groups as part of the larger parent trial. BMI, physical activity, fitness and diet were assessed at baseline, 6, 12 and 18 months. Separate adjusted mixed models were constructed using SAS version 9.4 (SAS Institute, Cary, NC). Results There was significant weight loss, increased physical activity, improved fitness and reduced caloric intake over time (p < 0.001). There were no significant differences in these outcome variables by obesity onset group. However, there was a significant group by time interaction for fitness (p = 0.001), with the adult onset making significantly greater gains in fitness from baseline to 6 months (p < 0.001); however, this difference was no longer present at 12 or 18 months. Conclusions With the exception of fitness at 6 months, weight loss, physical activity and diet did not differ between juvenile onset and adult onset participants, suggesting that those with juvenile onset obesity are equally responsive to a standard behavioral weight loss intervention in adulthood.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/osp4.55
Keywords: Obesity; dept.hms; physical activity; weight loss interventions

Developing an Appropriate Goalball Unit for Secondary Physical Education - Laughlin, Michael K.; Happel, Kathleen (Strategies, 2016)
Goalball, a sport designed for those with visual impairments, is a competitive and recreational sport enjoyed by athletes around the world. Students with and without visual impairments can experience positive outcomes when teachers appropriately include a goalball unit as part of their inclusive secondary physical education curriculum. This article aims to help teachers identify these outcomes through strategies that encourage student success and appreciation for the sport. A framework to implement a goalball unit is provided along with strategies to target skill, tactical and game-play development.
_eprint: https://doi.org/10.1080/08924562.2015.1111784
Keywords: dept.hms

What’s Going on Out There? An exploration of K–12 PE Curricular Models and Content Taught in Public Schools - Hodges, Michael; Laughlin, Michael; Brusseau, Timothy (The Physical Educator, 2018)
Little is known about which curricular models and activity units are being taught in public schools. This exploratory study examined the K–12 physical education (PE) content and curricular models being implemented. Supervisors of PE recruited from one northeastern state participated in a 25-item questionnaire. Descriptive statistics and frequencies were calculated. Sixty-nine of 92 questionnaires were usable and included in the data analysis. Findings suggest that few districts were using a curricular model at the elementary (K–5) level (27%). Another common response of adopted curricular models at the elementary level was Movement Education (17.6%). At the secondary level, No Model (35%) and Fitness Education (25.6%) were common responses. Specific units such as volleyball, basketball, and weight training yielded the highest responses, while field hockey, golf, archery, lacrosse, and tennis yielded the fewest responses. The findings suggest that K–12 PE curricula may not reflect current trends and mandates. The key determinants could be a lack of curricular model use and heavy reliance upon activities known to present challenges toward standards-based education (i.e., softball). Perhaps K–12 PE and PE preparation programs can connect to effectively articulate a curriculum, and adopt and train on curricular approaches aiming to increase teacher effectiveness and reach national standards.Subscribe to TPE
Number: 5
Keywords: Content; Curricular Models; PETE; Units; dept.hms

Assistive Technology: What Physical Educators Need to Know - Laughlin, Michael K., Nathan M., Murata, Michele, Gonnelli; Larranaga, John (Journal of Physical Education, Recreation & Dance, 2018)
Assistive technology supplements and supports the learning of students with disabilities in school and at home. Thanks to federal mandates, students with disabilities receive consideration for assistive technology devices and services — the tools and supports needed to achieve determined learning outcomes. Assistive technology devices and services operate as a process, ensuring students with disabilities receive optimal access to learning across all educational settings and subject areas. This article provides physical educators with a working knowledge of the assistive technology process along with recommendations for supporting their students with disabilities.
_eprint: https://doi.org/10.1080/07303084.2017.1417930
Keywords: dept.hms

Universal design for learning: Review and recommendations for EFL instruction - Timpe-Laughlin, Veronika; Laughlin, Michael K. (Inklusiver Englischunterricht. Impulse zur Unterrichtsentwicklung aus fachdidaktischer und sonderpädagogischer Perspektive, 2018)
Keywords: dept.hms

A Conceptual Framework for Tiered Intervention in Physical Education - Dauenhauer, Brian; Keating, Xiaofen; Lambdin, Dolly; Knipe III, Robert (Journal of Physical Education, Recreation & Dance, 2017)
Our goal as physical educators is to help all students develop the knowledge, skills and dispositions to be physically active for a lifetime. Despite efforts to address the diverse needs of students through quality physical education, the reality is that some students still need additional support beyond physical education to achieve their full potential. Response to intervention (RTI) is a proactive approach to educational-service delivery that relies on data-driven decision making to identify student needs and to tailor support. Traditionally, RTI has focused on addressing the needs of lower-performing students through tiered interventions. The purpose of this article is to review the basic principles of RTI, discuss how they have been applied in physical education thus far, and expand the conceptual framework so it can be used to address the needs of both higher- and lower-performing students.
_eprint: https://doi.org/10.1080/07303084.2017.1356769
Keywords: dept.hms

Development of a Scale Measuring Chinese Preservice Physical Education Teachers’ Beliefs About the Physical Education Profession - Fan, Yao; Keating, Xiaofen D.; Liu, Jingwen; Zhou, Ke; Shangguan, Rulan; Knipe, Robert (The Asia-Pacific Education Researcher, 2018)
This project aimed to develop a valid and reliable scale measuring Chinese preservice physical education teachers’ beliefs about the physical education profession (PPET-BPEP). The domains and items were created from a conceptual analysis of the previous literature and PPETs’ responses to an open-ended survey. Six experts in the field of physical education and educational psychology evaluated the content validity of the scale. The reliability and factorial validity of the scale were examined utilizing a sample of 696 Chinese PPETs. The PPET-BPEP scale with 12 items embedded in two domains revealed acceptable content validity, internal structure validity, and internal consistency. The two domains were labeled as “sense of calling” and “value of physical education profession” based on the shared content of items in each domain. We recommend using PPET-BPEP scale for PPET recruitment and preparation. The scale can also help establish teacher belief scales in other subject matters. Future validation of the scale is needed in different countries and institutions.
Keywords: Future physical education teacher; Professional beliefs; Survey development; Validity and reliability; dept.hms

Leadership: Athletes and Coaches in Sport - Academy, U. S. Sports (The Sport Journal, 2016)
Authors: Dr. Sharon P. Misasi*, Dr. Gary Morin and Lauren Kwasnowski Dr. Sharon P. Misasi is a Professor of Exercise Science at Southern Connecticut State University. Dr. Gary Morin is a Professor of Exercise Science, Assistant Athletic Trainer and Program Director of the Athletic Training Education Program. Lauren Kwasnowski is a Research assistant for this
Keywords: dept.hms

The relationship between heart rate variability and recovery heart rate in women - Latchman, P.; Gates, G.; Axtell, R.; Lunn, W.; Stachenfeld, N.; Meersman, R. De (Autonomic Neuroscience: Basic and Clinical, 2015)
Keywords: dept.hms

Dyspnea - Kreiger, J.; Niekrash, C.; Fitzgerald, C. (The Encyclopedia of Elder Care: The Comprehensive Resource on Geriatric Health and Social Care, 2017)
Praise for the Third Edition:“The third edition of this outstanding resource reflects the many advances in the care of older people that have occurred since the publication of the second edition…The vast bulk of the content is accessible and relevant to an international audience. The indexing and cross-referencing are excellent... Score: 5/5 stars."– Margaret Arthur, Nursing Standard"The information [in this book] is amazing. I reviewed topics in which I have expertise and was very satisfied. This is an excellent addition to my library and I will refer to it often, much like a medical dictionary... Score: 90, 4 Stars."–Doody's Medical Reviews“Provides 273 comprehensive, yet succinct, entries on a variety of topics related to elder care. In addition, many of the entries include see also references that help readers easily navigate the book. Recommended."–Choice: Current Reviews for Academic LibrariesThis expanded, one-of-a-kind reference of more than 250 entries provides a comprehensive guide to all of the essential elements of elder care across a breadth of health and social service disciplines. Responding to the needs of providers, directcare workers, family, and other caregivers, the diverse array of entries included in this encyclopedia recognize and address the complex medical, social, and psychological problems associated with geriatric care. In addition to a brief, accessible summary of each topic, entries include several key references, including web links and mobile apps for additional sources of information.This updated edition contains more than 30 new entries written by renowned experts that address a variety of elder care topics.New to the Fourth Edition:New entries addressing Ethics Consultation, Eye Disorders, Pain – Acute and Chronic, and many othersKey Features:Provides succinct descriptions of over 250 key topics for health and social service cliniciansOffers crucial information for elder care providers across all settings and disciplinesDistills current, evidence-based literature sourcesWritten by nationally recognized expert researchers and cliniciansIncludes links to useful websites and mobile apps
Keywords: dept.hms

Cognitive Performance Does not Limit Physical Activity Participation in the Lifestyle Interventions and Independence for Elders Pilot Study (LIFE-P) - Reid, K. F.; Walkup, M. P.; Katula, J. A.; Sink, K. M.; Anton, S.; Axtell, R.; Kerwin, D. R.; King, A. C.; Kramer, A. F.; Miller, M. E.; Myers, V.; Rosano, C.; et al. (The journal of prevention of Alzheimer's disease, 2017)
We examined whether multiple domains of baseline cognitive performance were associated with prospective physical activity (PA) adherence in the Lifestyle Interventions and Independence for Elders Pilot study (LIFE-P). The LIFE-P study was a ...
Keywords: dept.hms

The Effects of the VK Performance Insole on Running Economy in Highly-Trained Distance Runners: 518 Board# 1 May 30 1: 00 PM-3: 00 PM - Gregory, Robert W.; Lunn, William R.; Robertson, Marc I.; Axtell, Robert S. (Medicine & Science in Sports & Exercise, 2018)
Keywords: dept.hms

Rethinking Education from Patients' Perspectives - Harrison, Jill; Frampton, Susan; McNeal, Gloria J.; Todorova, Elena; Wahl, Carol; Kreiger, Joan (ABNF Journal, 2019)
Person-centered care (PCC) is a term used to describe an individualized approach to patient care that engages patients and families as partners in meaningful ways to create a comprehensive, collaborative, and customized plan and experience of care. Although some healthcare fields of study, such as the Quality and Safety Education for Nurses (QSEN) model, have adopted and integrated person-centered care concepts and competencies into their curricula, there remains a critical gap in higher education to systematically integrate person-centered care into the curricula and assessment of interprofessional healthcare fields of study. While the delivery of person-centered care by healthcare professionals requires education and training in PCC concepts, this training has primarily occurred on the job, without a standardized and comprehensive curriculum to systematically teach and assess PCC competencies to students in interprofessional healthcare and medical degree programs. Until recently, the educational foundations for healthcare disciplines were drawn primarily from biomedical, business, and nursing models, not from patients' points of view. In this article, we consider why teaching and evaluating PCC concepts should be the foundation of all interprofessional health education. We first review the perspectives of relevance to our argument and then advocate for a person-centered paradigm shift for interprofessional healthcare and medical education and training. Next, we argue that integrating and evaluating students' understanding and application of PCC concepts in all healthcarerelated disciplines will ensure that graduates receive the most current and relevant preparation for careers in healthcare and that this aligns with the expectations of patients as consumers.
Num Pages: 9 Place: Lisle, United States
Keywords: Curriculum; Education; Evaluation; GenderWatch; Interprofessional education; Patient; Person-centered care; Teaching method; Y; dept.hms; peer-reviewed; ⛔ No DOI found

State Physical Education Policy Changes From 2001 to 2016 - Dauenhauer, Brian; Keating, Xiaofen; Stoepker, Peter; Knipe, Robert (Journal of School Health, 2019)
ABSTRACT BACKGROUND State policies influence the quantity and quality of educational programs delivered in schools. This study examined state physical education policy changes from 2001 to 2016 by analyzing data reported in The Shape of the Nation Report . METHODS Policies related to state mandates for physical education, time/credit requirements, assessment and fitness testing requirements, adoption of state standards, and allowance of substitutions were analyzed over 5 editions of the report using repeated measures statistics. RESULTS A majority of state physical education‐related policies have not changed over the past 15 years despite calls by numerous public health agencies for enhanced physical education in schools. There was, however, a significant increase in the number of states adopting teaching standards and requiring assessment and fitness testing in physical education, mirroring a broader shift in education toward standards, assessment, and accountability. CONCLUSIONS Despite improved rigor in physical education through the adoption of standards and assessment practices, physical education continues to be marginalized in schools by a lack of curricular time and inappropriate substitution policies. Stronger policies are needed for physical education to have a substantial impact on school health.
Keywords: dept.hms; peer-reviewed

Teaching Students with Seizure Disorders - Laughlin, Michael, Nathan M. Murata (Case Studies in Adapted Physical Education, 2019)
The adapted physical educator (APE) at this high school has a tenth grader with epilepsy in his class. The student is assigned a paraprofessional to monitor and assist him. The APE plans an indoor soccer lesson, which allows for easier participation for another student in a wheelchair, as well as better monitoring for the student with epilepsy. With the lesson underway and the paraprofessional positioned nearby, the student has a seizure. Fortunately, the APE has had some training on recognizing seizures, and the paraprofessional is there to help. Wondering what would happen if they were not there when the student began having a seizure and how to explain it to the other students, the APE creates a seizure fact and protocol sheet.
Num Pages: 4
Keywords: dept.hms; peer-reviewed

Technological Applications in Physical Education - Murata, Nathan M., Michael K. Laughlin (Case Studies in Adapted Physical Education, 2019)
The physical education (PE) teacher at this high school learns how to integrate a high-tech assistive device into his class for a new student who is nonverbal and uses a walker or wheelchair. The school’s paraprofessional disagrees that the student should be permitted to use the device during PE because it could be broken. Even with ample accommodations for physical participation, the student still has difficulty communicating with her peers and becomes agitated. Upon consulting with the student’s special education teacher, the PE teacher learns about an app-based assistive technology that could be programmed so the student can prepare when and how to use the device safely throughout class. The student blossoms in PE, as well as socially, by being able to preprogram her device to communicate more closely to real time.
Num Pages: 5
Keywords: dept.hms

Effects of an adapted physical education training package on special education teacher instruction - Laughlin, Michael K.; Murata, Nathan M.; McDougall, Dennis (Behavioral Interventions, 2019)
This study investigated the impact of an adapted physical education training package on functional motor skill instruction of three special education teachers who instructed secondary students with low-incidence disabilities. The training package emphasized teachers' use of systematic prompting and specific reinforcement teaching strategies plus adapted physical education consultation. We used a multiple baseline design and collected data on the three teachers' use of systematic prompting and specific reinforcement plans during videotaped teaching trials. We also collected data on how teachers documented their instructional strategies, and we analyzed personal reflections that teachers wrote in the journals. Results indicated that with each of the three teachers, correctly implemented functional motor skill instructional performance improved after they completed the training package.
0 citations (Crossref) [2023-10-31] _eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/bin.1653
Keywords: dept.hms; functional motor skills; peer-reviewed; prompting; reinforcement; severe disabilities; special education

Deploying Video Analysis to Boost Instruction and Assessment in Physical Education - Laughlin, Michael K.; Hodges, Michael; Iraggi, Taylor (Journal of Physical Education, Recreation & Dance, 2019)
Physical educators are discovering the benefits of using video analysis to support their instruction and assessment. Slow-motion playback, zoom, and voice-over narration are just some of the features built into increasingly affordable mobile devices and applications that can easily be used by teachers to support student learning. Additionally, with the use of video technology, teachers are finding creative ways to provide instant motor-performance feedback which can be easily documented for assessment purposes. Yet, with any novel technology tool, internal and external challenges exist that may prevent teachers from realizing the myriad of benefits. This article provides a background on mobile video analysis tools, along with strategies to help physical educators discover ways to effectively implement this engaging technology into their curriculum.
7 citations (Crossref) [2023-10-31] _eprint: https://doi.org/10.1080/07303084.2019.1580637
Keywords: dept.hms; peer-reviewed

Sabbatical leave follow-up report Spring 2019 - Fede, Marybeth H. (2019)
Keywords: dept.hms; faculty_collection; sabbatical_report

The Essentials of Teaching Health Education: Curriculum, Instruction, and Assessment - Benes, Sarah (Human Kinetics, 2016)
"The Essentials of Teaching Health Education presents a skills-based approach to teaching K-12 health education–one that will prepare your students for success in school and beyond. You'll learn practical approaches to putting the contents in action and rely on an array of teaching and assessment strategies." –Publisher's website.
Keywords: Curricula; Health education; Standards; Training of; United States; United States; Health education; United States; Health education teachers; dept.hms; faculty_collection

Peripheral arterial disease: Exercise is medicineTM - Sorace, P.; Ronai, P.; Churilla, J.R. (ACSM's Health and Fitness Journal, 2010)
Learning objective: Peripheral arterial disease (PAD) significantly affects quality of life, particularly when doing activities such as walking and climbing stairs. In addition, persons with PAD have an increased risk for heart disease, stroke, and limb amputations. This article will summarize PAD, address exercise benefits specific to the disease, and discuss exercise training for those with PAD in both the clinical and the health and fitness setting. © 2010 Lippincott Williams & Wilkins.
1 citations (Crossref) [2023-10-31]
Keywords: Claudication; Functional Ability; Resistance Training; Stair Climbing; Walking; dept.hms

Proteins and amino acids: The repair blocks and their place in growth and recovery - Rodriguez, N.R.; Lunn, W. (Nutrient Timing: Metabolic Optimization for Health, Performance, and Recovery, 2011)
Journal Abbreviation: Nutr. Timing: Metab. Optim. for Health, Perform., and Recovery
Keywords: dept.hms

Weightlifting movements from full extension: The snatch and clean - DiSanto, M.; Valentine, G.; Boutagy, N. (Strength and Conditioning Journal, 2015)
Weightlifting movements require sufficient body speed to squat down and catch the barbell. Body speed can only be maximized if the correct positions are reached before the turnover and catch phases. The snatch from full extension (SFFE) and the clean from full extension (CFFE) allow the athlete to transition from the full extension position to a quick squat underneath the barbell. The SFFE and CFFE can be included into the warm-up or cooldown periods of a training session, focusing on the respective lifts. Correct body positions and speed, as opposed to barbell load, should be emphasized.
6 citations (Crossref) [2023-10-31]
Keywords: Body speed; Clean; Full extension; Snatch; Weightlifting; dept.hms

Associations Between Ankle-Brachial Index and Cognitive Function: Results From the Lifestyle Interventions and Independence for Elders Trial - Espeland, M.A.; Newman, A.B.; Sink, K.; Gill, T.M.; King, A.C.; Miller, M.E.; Guralnik, J.; Katula, J.; Church, T.; Manini, T.; Reid, K.F.; McDermott, M.M.; et al. (Journal of the American Medical Directors Association, 2015)
Objective: The objective of this study was to evaluate cross-sectional and longitudinal associations between ankle-brachial index (ABI) and indicators of cognitive function. Design: Randomized clinical trial (Lifestyle Interventions and Independence for Elders Trial). Setting: Eight US academic centers. Participants: A total of 1601 adults ages 70-89 years, sedentary, without dementia, and with functional limitations. Measurements: Baseline ABI and interviewer- and computer-administered cognitive function assessments were obtained. These assessments were used to compare a physical activity intervention with a health education control. Cognitive function was reassessed 24 months later (interviewer-administered) and 18 or 30 months later (computer-administered) and central adjudication was used to classify individuals as having mild cognitive impairment, probable dementia, or neither. Results: Lower ABI had a modest independent association with poorer cognitive functioning at baseline (partial r= 0.09; P < .001). Although lower baseline ABI was not associated with overall changes in cognitive function test scores, it was associated with higher odds for 2-year progression to a composite of either mild cognitive impairment or probable dementia (odds ratio 2.60 per unit lower ABI; 95% confidence interval 1.06-6.37). Across 2 years, changes in ABI were not associated with changes in cognitive function. Conclusion: In an older cohort sedentary individuals with dementia and with functional limitations, lower baseline ABI was independently correlated with cognitive function and associated with greater 2-year risk for progression to mild cognitive impairment or probable dementia. © 2015 AMDA - The Society for Post-Acute and Long-Term Care Medicine.
15 citations (Crossref) [2023-10-31]
Keywords: Aged; Aged; 80 and over; Ankle Brachial Index; Ankle-brachial index; Article; Cognition; Cognitive function; Cross-Sectional Studies; Dementia; Disability Evaluation; Exercise; Female; Geriatric Assessment; Health Education; Humans; Male; Mini Mental State Examination; Peripheral artery disease; Sedentary Lifestyle; United States; aged; ankle brachial index; clinical trial; cognition; controlled study; cross-sectional study; dementia; dept.hms; disability; episodic memory; executive function; exercise; female; follow up; geriatric assessment; health education; human; human experiment; learning; longitudinal study; male; mild cognitive impairment; multicenter study; normal human; physical activity; physical performance; randomized controlled trial; recall; sedentary lifestyle; spatial orientation; very elderly; working memory

Lower Wingate Test Power Outcomes from "all-Out" Pretest Pedaling Cadence Compared with Moderate Cadence - Lunn, W.R.; Zenoni, M.A.; Crandall, I.H.; Dress, A.E.; Berglund, M.L. (Journal of Strength and Conditioning Research, 2015)
The aim of the present study was to determine the effect of different pretest pedaling cadences on power outcomes obtained during the Wingate Anaerobic Test (WAnT). Vigorously exercising adult men (n 14, 24.9 ± 1.2 years) and women (n 14, 20.4 ± 0.6 years) participated in a randomized crossover study during which they performed the 30-second WAnT on a mechanically braked cycle ergometer (0.075 kg·kg-1 body weight) under 2 conditions. Participants pedaled maximally with an unloaded flywheel during 5 seconds before resistance was applied and the test began (FAST). In another trial, participants maintained a moderate cadence (80 revolutions per minute [rpm]) during 5 seconds before the test began (MOD). All other components of the WAnT were identical. Peak power (PP), mean power (MP), minimum power (MinP), fatigue index (%FAT), and maximum cadence during test were recorded. Comparisons were made using a 2 × 2 factorial repeated-measures analysis of variance. Regardless of gender, the FAST condition resulted in 22.2% lower PP (612.6 ± 33.0 W vs. 788.3 ± 43.5 W), 13.3% lower MP (448.4 ± 22.2 W vs. 517.2 ± 26.4 W), 11.7% lower MinP (280.9 ± 14.8 W vs. 318.3 ± 17.2 W), and 9.0% lower %FAT (53.5 ± 1.3% vs. 58.8 ± 1.5%) than MOD condition (p < 0.01; mean ± SD). Similar outcomes were observed within gender. The authors conclude that practitioners of the WAnT should instruct participants to maintain a moderate pedal cadence (∼80 rpm) during 5 seconds before the test commences to avoid bias from software sampling and peripheral fatigue. Standardizing the pretest pedal cadence will be important to exercise testing professionals who compare data with norms or generate norms for specific populations. © 2015 National Strength and Conditioning Association.
3 citations (Crossref) [2023-10-31]
Keywords: Adult; Bicycling; Cross-Over Studies; Exercise; Exercise Test; Fatigue; Female; Humans; Male; Young Adult; adult; anaerobic; controlled study; crossover procedure; cycling; dept.hms; ergometry; exercise; exercise test; fatigue; female; human; male; muscle; pathophysiology; peer-reviewed; physiology; procedures; randomized controlled trial; young adult

Association of accelerometry-measured physical activity and cardiovascular events in mobility-limited older adults: The LIFE (Lifestyle Interventions and Independence for Elders) study - Cochrane, S.K.; Chen, S.-H.; Fitzgerald, J.D.; Dodson, J.A.; Fielding, R.A.; King, A.C.; McDermott, M.M.; Manini, T.M.; Marsh, A.P.; Newman, A.B.; Pahor, M.; Tudor-Locke, C.; et al. (Journal of the American Heart Association, 2017)
Background–Data are sparse regarding the value of physical activity (PA) surveillance among older adults-particularly among those with mobility limitations. The objective of this study was to examine longitudinal associations between objectively measured daily PA and the incidence of cardiovascular events among older adults in the LIFE (Lifestyle Interventions and Independence for Elders) study. Methods and Results–Cardiovascular events were adjudicated based on medical records review, and cardiovascular risk factors were controlled for in the analysis. Home-based activity data were collected by hip-worn accelerometers at baseline and at 6, 12, and 24 months postrandomization to either a physical activity or health education intervention. LIFE study participants (n=1590; age 78.9±5.2 [SD] years; 67.2% women) at baseline had an 11% lower incidence of experiencing a subsequent cardiovascular event per 500 steps taken per day based on activity data (hazard ratio, 0.89; 95% confidence interval, 0.84-0.96; P=0.001). At baseline, every 30 minutes spent performing activities ≥500 counts per minute (hazard ratio, 0.75; confidence interval, 0.65-0.89 [P=0.001]) were also associated with a lower incidence of cardiovascular events. Throughout follow-up (6, 12, and 24 months), both the number of steps per day (per 500 steps; hazard ratio, 0.90, confidence interval, 0.85-0.96 [P=0.001]) and duration of activity ≥500 counts per minute (per 30 minutes; hazard ratio, 0.76; confidence interval, 0.63-0.90 [P=0.002]) were significantly associated with lower cardiovascular event rates. Conclusions–Objective measurements of physical activity via accelerometry were associated with cardiovascular events among older adults with limited mobility (summary score > 10 on the Short Physical Performance Battery) both using baseline and longitudinal data. © 2017 The Authors.
30 citations (Crossref) [2023-10-31]
Keywords: Accelerometry; Actigraphy; Age Factors; Aged; Aged; 80 and over; Aging; Article; Cardiovascular; Cardiovascular Diseases; Exercise; Exercise Therapy; Female; Fitness Trackers; Geriatric Assessment; Health Knowledge; Attitudes; Practice; Humans; Incidence; Male; Mobility Limitation; Patient Education as Topic; Physical activity; Predictive Value of Tests; Prognosis; Protective Factors; Risk Factors; Risk Reduction Behavior; Time Factors; United States; accelerometry; actimetry; activity tracker; age; aged; aging; attitude to health; cardiovascular disease; cardiovascular risk; clinical study; clinical trial; confidence interval; controlled study; dept.hms; devices; exercise; female; follow up; geriatric assessment; hazard ratio; health education; human; incidence; kinesiotherapy; lifestyle; major clinical study; male; medical record review; morbidity; multicenter study; patient education; phase 3 clinical trial; physical activity; physical mobility; predictive value; priority journal; prognosis; protection; randomized controlled trial; risk factor; risk reduction; time factor; very elderly; walking difficulty

Sports Injury Prevention: The Role of the Strength and Conditioning Coach - Talpey, S.W.; Siesmaa, E.J. (Strength and Conditioning Journal, 2017)
Prevention of sports injuries is a priority for sport stakeholders across the spectrum of training and competition. Achieving this objective requires a multidisciplinary approach with strength and conditioning coaches playing an important role in the process. When considering sports injury prevention strategies, the role of the strength and conditioning coach can extend beyond observing exercise technique and prescribing training to develop a robust and resilient athlete. This paper provides strength and conditioning coaches with a broad overview of the sports injury prevention process and outlines examples of how strength and conditioning coaches can work to promote and improve athlete safety. © 2017 National Strength and Conditioning Association.
17 citations (Crossref) [2023-10-31]
Keywords: Coaching; Sport safety; Sports medicine; dept.hms

Chocolate milk and endurance exercise recovery: protein balance, glycogen, and performance. - Lunn, William R; Pasiakos, Stefan M; Colletto, Megan R; Karfonta, Kirstin E; Carbone, John W; Anderson, Jeffrey M; Rodriguez, Nancy R (Medicine and science in sports and exercise, 2012)
Purpose: This study examined effects of fat-free chocolate milk (MILK) consumption on kinetic and cellular markers of protein turnover, muscle glycogen, and performance during recovery from endurance exercise. Methods: Male runners participated in two trials separated by 1 wk and consumed either MILK or a nonnitrogenous isocaloric carbohydrate (CHO) control beverage (CON) after a 45-min run at 65% of V̇O 2peak. Postexercise muscle protein fractional synthetic rate (FSR) and whole-body protein turnover were determined during 3 h of recovery using muscle biopsies and primed constant infusions of L-[ring-H5]phenylalanine and L-[1-C]leucine, respectively. Phosphorylation of translational signaling proteins and activity of proteolytic molecules were determined using Western blotting and enzymatic activity assays. Muscle glycogen was quantified, and treadmill time to exhaustion was determined after the recovery period. Results: Consuming MILK after exercise resulted in higher mixed muscle FSR with lower whole-body proteolysis and synthesis compared with CON (P ≤ 0.05). Phosphorylation of eIF4E-BP1 and FOXO3a was higher for MILK (P < 0.01), whereas Akt phosphorylation was lower during recovery regardless of dietary treatment (P < 0.05). Enzymatic activity assays indicated lower caspase-3 activity during recovery for MILK (P < 0.01) and higher 26S proteasome activity for CON (P < 0.01). Muscle glycogen was not affected by either dietary treatment; however, time to exhaustion was greater for MILK than for CON (P < 0.05). Conclusions: The effects of consumption of MILK after endurance exercise on FSR, signaling molecules of skeletal muscle protein turnover, leucine kinetics, and performance measures suggest unique benefits of milk compared with a CHO-only beverage. © 2012 by the American College of Sports Medicine.
66 citations (Crossref) [2023-10-31] Place: United States Lunn, William R. Exercise Science Department, Southern Connecticut State University, Moore Field House, Room 169, New Haven, CT 06515, USA. lunnw1@southernct.edu
Keywords: *Athletic Performance/ph [Physiology]; *Cacao/me [Metabolism]; *Milk/me [Metabolism]; *Muscle Proteins/bi [Biosynthesis]; *Physical Endurance/ph [Physiology]; ATP dependent 26S protease; Adaptor Proteins; Signal Transducing; Adaptor Proteins; Signal Transducing/me [Metabolism]; Adult; Animals; Athletic Performance; Cacao; Cell Cycle Proteins; Dietary Carbohydrates; Dietary Carbohydrates/me [Metabolism]; EIF4EBP1 protein; human; FOXO3 protein; human; Forkhead Box Protein O3; Forkhead Transcription Factors; Forkhead Transcription Factors/me [Metabolism]; Glycogen; Glycogen/an [Analysis]; Heart Rate; Heart Rate/ph [Physiology]; Humans; Male; Milk; Muscle Proteins; Muscle; Skeletal; Muscle; Skeletal/ch [Chemistry]; Muscle; Skeletal/me [Metabolism]; Muscle; Skeletal/ph [Physiology]; Oxygen Consumption; Oxygen Consumption/ph [Physiology]; Phosphoproteins; Phosphoproteins/me [Metabolism]; Phosphorylation; Physical Endurance; Proteasome Endopeptidase Complex; Proteasome Endopeptidase Complex/an [Analysis]; Protein synthesis; Proto-Oncogene Proteins c-akt; Proto-Oncogene Proteins c-akt/me [Metabolism]; Young Adult; adult; animal; article; athletic performance; biosynthesis; cacao; carbohydrate diet; chemistry; dept.hms; endurance; forkhead transcription factor; glycogen; heart rate; human; intracellular signaling; leucine kinetics; male; metabolism; milk; muscle glycogen; muscle protein; oxygen consumption; peer-reviewed; phosphoprotein; phosphorylation; physiology; proteasome; protein kinase B; proteolysis; signal transducing adaptor protein; skeletal muscle; time to exhaustion

A Prediction Of Vo2peak: Least Intrusive Model In Males 18-35 Years: 2325: Board #202 June 2 3:30 PM - 5:00 PM. - Crandall, Ian; Finn, Joan; Latchman, Peter; Thiel, Robert; Mugno, Raymond; Zenoni, Maria; Sollanek, Kurt; Axtell, Robert (Medicine & Science in Sports & Exercise, 2011)
0 citations (Crossref) [2023-10-31] Place: (C) 2011 American College of Sports Medicine
Keywords: dept.hms; dept.mat

Gradual vs. Maximal Acceleration: Their Influence on the Prescription of Maximal Speed Sprinting in Team Sport Athletes. - Young, Warren B; Duthie, Grant M; James, Lachlan P; Talpey, Scott W; Benton, Dean T; Kilfoyle, Anthony (Sports, 2018)
The primary purpose of this study was to determine if a difference existed between peak speed attained when performing a sprint with maximal acceleration versus from a gradual build-up. Additionally, this investigation sought to compare the actual peak speed achieved when instructed to reach 75% and 90% of maximum speed. Field sport athletes (n = 21) performed sprints over 60 m under the experimental conditions, and the peak speed was assessed with a radar gun. The gradual build-up to maximum speed (8.30 +/- 0.40 m.s-1) produced the greater peak speed (effect size = 0.3, small) than the maximum acceleration run (8.18 +/- 0.40 m.s-1), and the majority of participants (62%) followed this pattern. For the sub-maximum runs, the actual mean percentage of maximum speed reached was 78 +/- 6% for the 75% prescribed run and 89 +/- 5% for the 90% prescription. The errors in attaining the prescribed peak speeds were large (~15%) for certain individuals, especially for the 75% trial. Sprint training for maximum speed should be performed with a gradual build-up of speed rather than a maximum acceleration. For sub-maximum interval training, the ability to attain the prescribed target peak speed can be challenging for field sport athletes, and therefore where possible, feedback on peak speeds reached should be provided after each repetition.
4 citations (Crossref) [2023-10-31] Place: Switzerland Young, Warren B. School of Health and Life Sciences, Federation University, Ballarat 3350, Australia. w.young@federation.edu.au. Duthie, Grant M. School of Exercise Science, Australian Catholic University, North Sydney 2060, Australia. grant.duthie@acu.edu.au. James, Lachlan P. School of Health and Life Sciences, Federation University, Ballarat 3350, Australia. l.james@latrobe.edu.au. James, Lachlan P. Department of Rehabilitation, Nutrition and Sport, School of Allied Health, La Trobe University, Melbourne 3086, Australia. l.james@latrobe.edu.au. Talpey, Scott W. School of Health and Life Sciences, Federation University, Ballarat 3350, Australia. talpeys1@southernct.edu. Talpey, Scott W. Exercise Science Department, Southern Connecticut State University, New Haven, CT 06515, USA. talpeys1@southernct.edu. Benton, Dean T. Atletico, Melbourne, Australia. dbenton@atletico.com.au. Kilfoyle, Anthony. School of Health and Life Sciences, Federation University, Ballarat 3350, Australia. tonykilfoyle@hotmail.com.
Keywords: Acceleration; Conditioning; Programming; Team sport; dept.hms; peer-reviewed

Social determinants of health: the how, who, and where screenings are occurring; a systematic review. - O'Brien, Kyle H (Social work in health care, 2019)
Screening for social determinants of health allows health care teams to assess and address social factors that influence one's health, mental health, and access to care. These social factors include poverty, health literacy, social support, exposure to trauma, food insecurity, and housing instability. The objective of this study was to examine what screening tools for social determinants of health are being used, in what contexts, and with what populations. Findings suggest that health literacy is the most commonly screened for, followed by trauma history, social support, food insecurity and housing across diverse contexts and populations. Results from this study can be used to inform providers of available screening tools and resources that can be readily utilized in practice.
32 citations (Crossref) [2023-10-31] Place: United States O'Brien, Kyle H. School of Health and Human Services, Department of Social Work, Southern Connecticut State University, New Haven, CT, USA. O'Brien, Kyle H. Department of Health and Movement Sciences, Southern Connecticut State University, New Haven, CT, USA.
Keywords: *Food Supply/sn [Statistics & Numerical Data]; *Health Literacy/sn [Statistics & Numerical Data]; *Health Services Accessibility/sn [Statistics & Numerical Data]; *Health Status Indicators; *Housing/sn [Statistics & Numerical Data]; *Poverty/sn [Statistics & Numerical Data]; *Social Determinants of Health/sn [Statistics & Numerical Data]; Humans; dept.hms; peer-reviewed

Reducing sedentary behavior versus increasing moderate-to-vigorous intensity physical activity in older adults: a 12-week randomized, clinical trial - Gibbs, Bethany Barone; Brach, Jennifer S.; Byard, Tom; Creasy, Seth; Davis, Kelliann K.; McCoy, Stephanie; Peluso, Anna; Rogers, Renee J.; Rupp, Kristie; Jakicic, John M. (Journal of Aging and Health, 2016)
Objective: To compare the effects of behavioral interventions targeting decreased sedentary behavior versus increased moderate-to-vigorous intensity physical ac...
45 citations (Crossref) [2023-10-31] Publisher: SAGE PublicationsSage CA: Los Angeles, CA
Keywords: dept.hms

Perceptions of motor effort is not dependent on muscle mass or extremity - John, Emmanuel B; Frames, Christopher W; Soangra, Rahul; Gregory, Robert W (The 1st Annual Waldron College Interprofessional Symposium & Expo, 2014)
Citation Key Alias: lens.org/148-831-350-624-548
Keywords: dept.hms; ⛔ No DOI found

Actigraphy features for predicting mobility disability in older adults - Kheirkhahan, Matin; Tudor-Locke, Catrine; Axtell, Robert; Buman, Matthew P.; Fielding, Roger A.; Glynn, Nancy W.; Guralnik, Jack M.; King, Abby C.; White, Daniel K.; Miller, Michael E.; Siddique, Juned; Brubaker, Peter; et al. (Physiological Measurement, 2016)
Actigraphy has attracted much attention for assessing physical activity in the past decade. Many algorithms have been developed to automate the analysis process, but none has targeted a general model to discover related features for detecting or predicting mobility function, or more specifically, mobility impairment and major mobility disability (MMD). Men (N = 357) and women (N = 778) aged 70-89 years wore a tri-axial accelerometer (Actigraph GT3X) on the right hip during free-living conditions for 8.4 +/- 3.0 d. One-second epoch data were summarized into 67 features. Several machine learning techniques were used to select features from the free-living condition to predict mobility impairment, defined as 400 m walking speed ¡0.80 m s(-1). Selected features were also included in a model to predict the first occurrence of MMD-defined as the loss in the ability to walk 400 m. Each method yielded a similar estimate of 400 m walking speed with a root mean square error of similar to 0.07 m s(-1) and an R-squared values ranging from 0.37-0.41. Sensitivity and specificity of identifying slow walkers was approximately 70% and 80% for all methods, respectively. The top five features, which were related to movement pace and amount (activity counts and steps), length in activity engagement (bout length), accumulation patterns of activity, and movement variability significantly improved the prediction of MMD beyond that found with common covariates (age, diseases, anthropometry, etc). This study identified a subset of actigraphy features collected in free-living conditions that are moderately accurate in identifying persons with clinically-assessed mobility impaired and significantly improve the prediction of MMD. These findings suggest that the combination of features as opposed to a specific feature is important to consider when choosing features and/or combinations of features for prediction of mobility phenotypes in older adults.
Citation Key Alias: lens.org/144-715-377-748-547 tex.eissn: [object Object] tex.orcid-numbers: [object Object] tex.unique-id: [object Object]
Keywords: Accelerometers; Actigraphy; Analysis process; Artificial intelligence; Data mining; Disability; Feature extraction; Forecasting; Free livings; General model; Learning systems; Living conditions; Mean square error; Older adults; Patient monitoring; Physical activity; Sedentary; Walking aids; Walking speed; aging; data mining; dept.hms; disability; machine learning; physical activity; sedentary; ⚠️ Invalid DOI

Great games that disappeared - Rauschenbach, James; Swartz, Daniel R (Strategies: a journal for physical and sport educators, 2016)
Sometimes through a single person's efforts, a new and innovative game is developed and promoted locally. Occasionally, circumstances cause these games to remain on a local level without being adopted by mainstream physical educators and physical activity professionals. Unfortunately, some educators tend to stick to what they know and teach traditional games and sports. This practice has left little room for unique and innovative games such as tchoukball and hocker to contribute to physical education curriculum. This article describes the history of how each of these games was developed and promoted. Rules, equipment and game-play strategies are provided. ©, Copyright Taylor & Francis.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/100-180-565-266-823 tex.type: [object Object]
Keywords: dept.hms

Fish oil supplementation is associated with improved physical function and reduced mobility disability - Gundermann, D. M.; Hire, D. G.; Ambrosius, W. T.; Kritchevsky, S. B.; Pahor, M.; Axtell, R. S.; Newman, A. B.; Manini, T. M. (Gerontologist, 2015)
tex.eissn: 1758-5341 tex.unique-id: ISI:000374222703311
Keywords: dept.hms; peer-reviewed; ⛔ No DOI found

The relationship between indices of parasympathetic nervous activity and cardiovascular health in men - Latchman, P; Gates, Gregory J; Thiel, Robert; Hannah, C; Stachenfeld, Nina S; Meersman, R De (Autonomic Neuroscience: Basic and Clinical, 2015)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/000-274-329-107-531 tex.type: [object Object]
Keywords: dept.hms

Effectiveness of a hybrid classroom in the delivery of medical terminology course content relative to a traditional classroom format - Martin, Jeffrey S; Kreiger, Joan E; Apicerno, Amy L (Journal of the Scholarship of Teaching and Learning, 2015)
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/114-653-079-465-267 tex.type: [object Object]
Keywords: dept.hms

Psychoanalysis, artistic obsession, and artistic motivation: the study of pathography. - Kemler, David S (Perceptual and Motor Skills, 2014)
A modern assessment of Freud's conceptualization of the creative process focusing on drives, ego psychology, and object relation theory is presented. 40 artists and musicians were interviewed employing 13 open-ended questions to provoke responses historically associated with the theoretical conceptualizations of Freud and post-Freudian theory related to the creative process. Creative process was defined as internal object relations that motivate the external connection between artist and the creative work. Measured responses concerning purpose and understanding; motivation before, during, and after performance; obstacles in performance; and needs through the creative process were assessed. Cluster analysis segregated the participants into high, medium, and low agreement groups based on similarity of responses. A multivariate stepwise regression revealed four questions (enlightenment, drives, obstacles, and ought self discrepancies) accounted for 83.9% of the variance. A post hoc discriminant function analysis identified 82.5% of the population to their correct groups. The findings support Spitz's (2005) suggestion that we regard “drives, ego psychology, and object relation theory not as separate approaches but as parts of a whole with varying stresses or accents” (p. 503).
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/012-434-150-540-250 tex.type: [object Object]
Keywords: Adult; Art; Cluster Analysis; Creativity; Drive; Female; Freudian Theory; Humans; Male; Middle Aged; Motivation; Multivariate Analysis; Music; Object Attachment; Obsessive Behavior; Psychoanalytic Theory; Regression Analysis; adult; art; article; cluster analysis; creativity; dept.hms; drive; female; human; male; middle aged; motivation; multivariate analysis; music; object relation; obsession; psychoanalytic theory; psychological aspect; regression analysis

PASS: creating physically active school systems. - Ciotto, Carol M; Fede, Marybeth H (The Journal of Physical Education, Recreation & Dance, 2014)
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/119-394-176-908-486 tex.type: [object Object]
Keywords: dept.hms

Entry-level athletic trainers' self-confidence in clinical skill preparedness for treating athletic and emergent settings populations - Morin, Gary E; Misasi, Sharon; Davis, Charles; Hannah, Corey; Rothbard, Matthew (Athletic training education journal, 2014)
7 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/030-052-052-807-125 tex.type: [object Object]
Keywords: dept.hms

Spontaneous baroreflex sensitivity in young normotensive African-American women - Latchman, Peter; Gates, Gregory J; Axtell, Robert S; Pereira, Jason; Bartels, Matthew N; Meersman, Ronald Edmond De (Clinical Autonomic Research, 2013)
6 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/109-712-863-816-776 tex.type: [object Object]
Keywords: African American; European American; adult; article; body mass; breathing rate; clinical article; controlled study; dept.hms; diastolic blood pressure; family history; female; human; hypertension; physical activity; pressoreceptor reflex; race difference; systolic blood pressure

Make your own fitness: the suspension training project - Rauschenbach, Jim; Morrell, Katie; Ridley, Ben; Walsh, Brittany (Strategies: a journal for physical and sport educators, 2013)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/041-506-613-515-206 tex.type: [object Object]
Keywords: dept.hms

Promoting physical activity for elders with compromised function: the Lifestyle Interventions and Independence for Elders (LIFE) Study physical activity intervention - Rejeski, W. Jack; Axtell, Robert; Fielding, Roger; Katula, Jeffrey; King, Abby C.; Manini, Todd M.; Marsh, Anthony P.; Pahor, Marco; Rego, Alvito; Tudor-Locke, Catrine; Newman, Mark; Walkup, Michael P.; et al. (Clinical Interventions in Aging, 2013)
The Lifestyle Interventions and Independence for Elders (LIFE) Study is a Phase III randomized controlled clinical trial (Clinicaltrials.gov identifier: NCT01072500) that will provide definitive evidence regarding the effect of physical activity (PA) on major mobility disability in older adults (70-89 years old) who have compromised physical function. This paper describes the methods employed in the delivery of the LIFE Study PA intervention, providing insight into how we promoted adherence and monitored the fidelity of treatment. Data are presented on participants' motives and self-perceptions at the onset of the trial along with accelerometry data on patterns of PA during exercise training. Prior to the onset of training, 31.4% of participants noted slight conflict with being able to meet the demands of the program and 6.4% indicated that the degree of conflict would be moderate. Accelerometry data collected during PA training revealed that the average intensity - 1,555 counts/minute for men and 1,237 counts/minute for women - was well below the cutoff point used to classify exercise as being of moderate intensity or higher for adults. Also, a sizable subgroup required one or more rest stops. These data illustrate that it is not feasible to have a single exercise prescription for older adults with compromised function. Moreover, the concept of what constitutes “moderate” exercise or an appropriate volume of work is dictated by the physical capacities of each individual and the level of comfort/stability in actually executing a specific prescription.
36 citations (Crossref) [2023-10-31] tex.orcid-numbers: Buford, Thomas W/0000-0002-9541-4358 Handberg, Eileen/0000-0002-7805-9577 Newman, Mark/0000-0002-0444-8246 tex.researcherid-numbers: Buford, Thomas W/B-1111-2011 Katula, Jeffrey/K-5905-2013 tex.unique-id: ISI:000324170300001
Keywords: Accelerometry; Aged; Aged; 80 and over; Aging; Compromised physical function; Exercise; Female; Health Promotion; Humans; Independent Living; Male; Mobility Limitation; Older adults; Physical disability; Qualitative Research; Risk Reduction Behavior; Sex Distribution; accelerometry; aged; aging; article; autoregulation; body mass; compromised physical function; computer interface; computer program; conceptual framework; controlled study; dept.hms; education; elderly care; ethnicity; exercise intensity; female; health education; human; human experiment; lifestyle; male; motor performance; normal human; older adults; phase 3 clinical trial; physical activity; physical capacity; physical disability; quality of life; randomized controlled trial; semi structured interview; sex difference; social behavior; social environment

“The greatest game ever”: swatball - Swartz, Daniel R; Rauschenbach, Jim (Strategies: a journal for physical and sport educators, 2013)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/011-715-466-336-656 tex.type: [object Object]
Keywords: dept.hms

Physical activity strategies for improved cognition: the mind/body connection - Fede, Marybeth H (Strategies: a journal for physical and sport educators, 2012)
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/139-494-321-951-178 tex.type: [object Object]
Keywords: dept.hms

Potential impact of a 500-mL water bolus and body mass on plasma osmolality dilution - Sollanek, Kurt J.; Kenefick, Robert W.; Cheuvront, Samuel N.; Axtell, Robert S. (European Journal of Applied Physiology, 2011)
A methodological discrepancy exists in the hydration assessment literature regarding the establishment of euhydration, as some investigations utilize a prehydration technique, while others do not (overnight fluid/food fast). However, the degree that plasma osmolality (Posm) dilutes when using the pre-hydration method and how body mass/composition might influence the results is not known. Thirty subjects (22 M, 8 F; 20 ± 2 years (mean ± SD); 1.8 ± 0.1 m; 75.8 ± 13.5 kg) had P osm measured after an 8-h food and fluid fast (overnight fast) and 90 min after a 500-mL (4-9 mL/kg) water bolus (prehydration). From pre- to post-bolus, participants' P osm declined from 297 ± 3.5 to 295 ± 3.8 mmol/kg (p<0.05; Δ -1.7 ± 3.5 mmol/kg). One-third of the sample diluted to more than -3 mmol/kg. The effect of body mass on P osm dilution was investigated by comparing dilution in the ten lightest (62.8 ± 3.4 kg) and heaviest (92.0 ± 9.8 kg) participants; however, the change between the light (Δ -1.9 ± 3.8 mmol/kg) versus heavy groups (Δ -1.1 ± 3.0 mmol/kg) was not different (p>0.05). The correlation between body mass or total body water and change in P osm was weak (p>0.05), as was the correlation between relative fluid intake based on mass and change in P osm (p>0.05). The two methodologies appear to produce similar P osm values when measured in most individuals. However, the potential for significant dilution (>3 mmol/kg) should be considered when choosing the pre-hydration methodology. © Springer-Verlag (outside the USA) 2011.
17 citations (Crossref) [2023-10-31] Citation Key Alias: pop00120 tex.type: [object Object]
Keywords: Adolescent; Adult; Blood; Blood Chemical Analysis; Body Weight; Dehydration; Drinking; Female; Fluid intake; Humans; Hydration assessment; Hypohydration; Male; Osmolar Concentration; SCSU-student; Total body water; Water; Water-Electrolyte Balance; Young Adult; adolescent; adult; article; blood; blood analysis; body weight; clinical trial; dehydration; dept.hms; drinking; drug effect; electrolyte balance; female; human; male; metabolism; osmolarity; physiology; water

Impaired autonomic function in normotensive obese children - Latchman, Peter L; Mathur, Madhu; Bartels, Matthew N; Axtell, Robert S; Meersman, Ronald E De (Clinical Autonomic Research, 2011)
Purpose To evaluate baroreflex sensitivity and autonomic control in a cohort of normotensive obese (OB) children. Method A cross-sectional investigation, in which, baroreflex sensitivity and autonomic control were evaluated using transfer function and power spectral density analysis (PSDA) of the electrocardiogram and beat-to-beat blood pressures in normotensive OB children and normal weight normotensive controls. All methods used were noninvasive and data were captured while seated and at rest. Results The OB and control subjects non-obese (NO) were of similar age (OB 9.1 ± 1.9 years vs.NO9.2 ± 1.4 years). The OB group was classified as having a BMI greater than the 95th percentile adjusted for age and gender, and a NO group with a BMI at or less than the 95th percentile (BMI percentile OB. 97.5 ± 1.3 vs. NO 58.5 ± 24.1). Both groups had similar normotensive blood pressures. T tests revealed that baroreflex sensitivity and HFRR were significantly reduced in the OB 9.2 ± 2.7 vs. 15.2 ± 4.7 (ms/mmHg) and 6.7 ± 1.1 vs. 8.2 ± 1.1 ms 2, respectively, while LF SBP and LF/HF ratio were significantly increased in the OB 11.9 ± 5.6 vs. 8.2 ± 4.7 mmHg 2 and 1.2 ± 0.7 vs. 0.54 ± 0.3, respectively. Conclusions Normotensive OB children exhibited significantly reduced baroreflex sensitivity, parasympathetic control as well as increased sympathetic control when compared with healthy, NO controls. Findings in this investigation raise the awareness that autonomic dysfunction is present in young OB normotensive children. © Springer-Verlag 2011.
29 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/000-898-861-083-084 tex.type: [object Object]
Keywords: Autonomic Nervous System; Autonomic modulation; Baroreflex sensitivity; Blood Pressure; Child; Cross-Sectional Studies; Female; Humans; Male; Normotensive; Obese children; Obesity; article; autonomic dysfunction; blood pressure; blood pressure measurement; body mass; body weight; child; clinical article; controlled study; dept.hms; electrocardiogram; female; human; male; obesity; pressoreceptor reflex; school child; sensitivity analysis

Wingate test peak power is positively correlated to peak torque and power in bilateral isokinetic knee dynamometry - Lunn, William R; Zenoni, Maria; Crandall, Ian; Berglund, Michelle; Dress, Ashley; Wiley, Charlie; Axtell, Robert S (The FASEB Journal, 2011)
Citation Key Alias: lens.org/159-510-863-665-515 tex.type: [object Object]
Keywords: dept.hms; peer-reviewed; ⛔ No DOI found

Evaluation of an interdisciplinary physically active lifestyle course model - Fede, Marybeth H. (Research Quarterly for Exercise and Sport, 2010)
tex.unique-id: ISI:000275436700043
Keywords: dept.hms; peer-reviewed; ⛔ No DOI found

Pedagogical consideration: how do I teach to my students? - Xiang, Ping; Yang, Jinjin (Research Quarterly for Exercise and Sport, 2010)
tex.unique-id: ISI:000275436700013
Keywords: dept.hms; peer-reviewed; ⛔ No DOI found

Seeing to hear? Patterns of gaze to speaking faces in children with autism spectrum disorders. - Irwin, Julia R; Brancazio, Lawrence (Frontiers in Psychology, 2014)
Using eye-tracking methodology, gaze to a speaking face was compared in a group of children with autism spectrum disorders (ASD) and a group with typical development (TD). Patterns of gaze were observed under three conditions: audiovisual (AV) speech in auditory noise, visual only speech and an AV non-face, non-speech control. Children with ASD looked less to the face of the speaker and fixated less on the speakers' mouth than TD controls. No differences in gaze were reported for the non-face, non-speech control task. Since the mouth holds much of the articulatory information available on the face, these findings suggest that children with ASD may have reduced access to critical linguistic information. This reduced access to visible articulatory information could be a contributor to the communication and language problems exhibited by children with ASD.
23 citations (Crossref) [2023-10-31] Place: Switzerland Irwin, Julia R. Haskins Laboratories New Haven, CT, USA ; Department of Psychology, Southern Connecticut State University New Haven, CT, USA. Brancazio, Lawrence. Haskins Laboratories New Haven, CT, USA ; Department of Psychology, Southern Connecticut State University New Haven, CT, USA.
Keywords: Audiovisual speech perception; Autism spectrum disorders; Communication development; Eyetracking; Lipreading; Speech in noise; dept.hls; dept.hms; dept.psy; peer-reviewed

Validity and reliability of the lode excalibur sport cycle ergometer for the wingate anaerobic test - Lunn, William R.; Axtell, Robert S. (The Journal of Strength & Conditioning Research, 2019)
Lunn, WR and Axtell, RS. Validity and reliability of the Lode Excalibur Sport cycle ergometer for the Wingate Anaerobic Test. J Strength Cond Res XX(X): 000–000, 2019—Although multiple testing devices advertise Wingate Anaerobic Test (WAnT), capability, reliability, and validity data are sparse. The purpose was to determine whether the Lode Excalibur Sport cycle ergometer is a reliable and valid instrument to conduct the 30-second WAnT when compared with the Monark 894e Peak Bike ergometer. Recreationally active men (n = 49; 20.6 ± 2.5 years; 1.75 ± 0.07 m; and 79.1 ± 9.8 kg) completed four 30-second WAnTs: 2 each on the Lode and the Monark ergometers for peak power (PP), mean power (MP), minimum power (MinP), fatigue index (FI), and peak cadence (vmax) measurement. Interday and interunit correlation, multivariate analysis of variance, regression, and Bland-Altman analysis determined reliability and validity. Cohen's d was used to determine effect size. Relative reliability (intraclass correlation coefficient) with 95% confidence interval for Monark and Lode was very high for PP, MP, MinP, and vmax and high for FI (r > 0.83; coefficient of variation ≤ 27.0%; p < 0.01). Interunit correlation was strong for PP, MP, MinP, and vmax (r > 0.75; p < 0.001) and moderate for FI (p = 0.001). Lode PP and FI values were significantly less (p < 0.001; d > 1.18) and MinP, MP, and vmax significantly greater (p ≤ 0.001; d > 0.51) than Monark. Proportional bias was demonstrated for all variables (p < 0.04; d > 2.68) except vmax. The Lode ergometer reliably provides WAnT outcomes and correlates well to the Monark ergometer. However, differences in power values and proportional bias between differently braked instruments prevent use of the Lode ergometer for comparison of WAnT data with normative data generated by the Monark ergometer.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lunnValidityReliabilityLode2019
Keywords: dept.hms; peer-reviewed

Feasibility and safety of a group physical activity program for youth with type 1 diabetes - Ash, Garrett I.; Joiner, Kevin L.; Savoye, Mary; Baker, Julien S.; Gerosa, James; Kleck, Emma; Patel, Neha S.; Sadler, Lois S.; Stults-Kolehmainen, Matthew; Weinzimer, Stuart A.; Grey, Margaret (Pediatric Diabetes, 2019)
Background/ObjectiveMany adolescents with type 1 diabetes do not achieve 60 minutes of daily moderate-to-vigorous intensity physical activity (MVPA). Recognizing the importance of peer influence during adolescence, we evaluated the feasibility and safety of a group MVPA intervention for this population. MethodsEighteen adolescents with type 1 diabetes (age 14.12 .3 years, female 67%, black or Latino 67%, median body mass index 92%ile, A1c 79.925.1 mmol/mol, 9.5 +/- 2.3%). Intervention sessions (35minutes MVPA and 45minutes discussion) occurred 1x/week for 12weeks. Feasibility and safety metrics were enrollment, completion of intervention and assessments, cost, and hypoglycemia rates. Participants completed MVPA (accelerometry), and exploratory nutritional, psychosocial, clinical, and fitness variable assessments at baseline, 3 months, and 7 months. Hedges' effect sizes were calculated. ResultsEnrollment was 16%, and intervention completion was 56%. Assessment completion at 7 months was 67% for MVPA, nutrition, and fitness, 83% for psychosocial assessments, and 94% for clinical assessments. Cost was $1241 per completing participant. One episode of mild hypoglycemia occurred during the sessions (0.6%). Self-reported daily fruit/vegetable servings (d=-0.72) and diabetes self-management behaviors decreased over time (d=-0.40). In the 10 completers, endurance run score improved (d=0.49) from low baseline levels, while systolic blood pressure decreased (d=-0.75) and low-density lipoprotein increased (d=0.49) but stayed within normal ranges. ConclusionsThe protocol for the group MVPA intervention was safe and had some feasibility metrics meriting further investigation. MVPA levels and glycemic control remained suboptimal, suggesting the need for more intensive interventions for this population.
8 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/065-217-762-885-796 tex.eissn: [object Object] tex.orcid-numbers: [object Object] tex.unique-id: [object Object]
Keywords: Accelerometry; Adolescent; Age Factors; Article; Black person; Blood Glucose; Child; Combined Modality Therapy; Diabetes Mellitus; Type 1; Diet Records; Exercise; Exercise Therapy; Feasibility Studies; Female; Group Processes; Health Behavior; Hispanic; Humans; Male; Young Adult; accelerometry; adolescent; adult; adverse event; age; behavior; blood; body mass; child; clinical article; clinical outcome; clinical protocol; clinical trial; cost; dept.hms; diabetes mellitus; disease severity; endurance; exercise; feasibility study; female; fitness; food intake; fruit; glucose blood level; glycated hemoglobin A; group process; health behavior; health program; human; hypoglycemia; insulin dependent diabetes mellitus; kinesiotherapy; low density lipoprotein; male; medical record; metabolism; multimodality cancer therapy; nutritional assessment; patient safety; peer-reviewed; physical activity; physiology; priority journal; procedures; psychosocial care; scoring system; self care; self report; systolic blood pressure; type 1; vegetable; young adult

Stakeholders' support of CSPAP sustainability after a three-year PEP grant - Egan, Catherine A.; Karp, Grace Goc; Berei, Catherine (Research Quarterly for Exercise and Sport, 2019)
tex.address: 2-4 PARK SQUARE, MILTON PARK, ABINGDON OX14 4RN, OXON, ENGLAND tex.affiliation: Egan, Catherine A.; Karp, Grace Goc, Univ Idaho, Moscow, ID 83843 USA. Berei, Catherine, Southern Connecticut State Univ, New Haven, CT 06515 USA. tex.author-email: eganca@uidaho.edu tex.da: 2019-10-31 tex.doc-delivery-number: HT4YY tex.eissn: 2168-3824 tex.journal-iso: Res. Q. Exerc. Sport tex.number-of-cited-references: 0 tex.publisher: ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD tex.research-areas: Social Sciences - Other Topics; Psychology; Sport Sciences tex.times-cited: 0 tex.type: Meeting abstract tex.unique-id: ISI:000464570500141 tex.usage-count-last-180-days: 1 tex.usage-count-since-2013: 1 tex.web-of-science-categories: Hospitality, Leisure, Sport & Tourism; Psychology, Applied; Psychology; Sport Sciences
Keywords: dept.hms; peer-reviewed; ⛔ No DOI found

Sport specialization: A survey of collegiate and professional athletes - Misasi, Sharon P.; Morin, Gary; Swartz, Daniel Reid (Research Quarterly for Exercise and Sport, 2019)
tex.address: 2-4 PARK SQUARE, MILTON PARK, ABINGDON OX14 4RN, OXON, ENGLAND tex.affiliation: Misasi, Sharon P.; Morin, Gary; Swartz, Daniel Reid, Southern Connecticut State Univ, New Haven, CT 06515 USA. tex.author-email: misasis1@southernct.edu tex.da: 2019-10-31 tex.doc-delivery-number: HT4YY tex.eissn: 2168-3824 tex.journal-iso: Res. Q. Exerc. Sport tex.number-of-cited-references: 0 tex.publisher: ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD tex.research-areas: Social Sciences - Other Topics; Psychology; Sport Sciences tex.times-cited: 0 tex.type: Meeting abstract tex.unique-id: ISI:000464570500216 tex.usage-count-last-180-days: 0 tex.usage-count-since-2013: 1 tex.web-of-science-categories: Hospitality, Leisure, Sport & Tourism; Psychology, Applied; Psychology; Sport Sciences
Keywords: dept.hms; peer-reviewed; ⛔ No DOI found

Championing CSPAPs: studies of targeted program implementers and advocates - Webster, Collin A.; Moore, Chanta; Orendorff, Karie Lee; Taunton, Sally; Mindrila, Diana; Stewart, Gregory; Lee, Joey A.; Welk, Gregory J.; Foster, Lorraine Lanningham; Gentile, Douglas; Vazou, Spyridoula; Liechty, Laura; et al. (Research Quarterly for Exercise and Sport, 2019)
tex.eissn: 2168-3824 tex.unique-id: ISI:000464570500004
Keywords: dept.hms; peer-reviewed; ⛔ No DOI found

Effect of hospitalizations on physical activity patterns in mobility-limited older adults - Wanigatunga, Amal A.; Gill, Thomas M.; Marsh, Anthony P.; Hsu, Fang-Chi; Yaghjyan, Lusine; Woods, Adam J.; Glynn, Nancy W.; King, Abby C.; Newton, Jr., Robert L.; Fielding, Roger A.; Pahor, Marco; Manini, Todd M.; et al. (Journal of the American Geriatrics Society, 2019)
OBJECTIVES: To evaluate the effect of hospitalizations on patterns of sedentary and physical activity time in mobility-limited older adults randomized to structured physical activity or health education. DESIGN: Secondary analysis of investigator-blinded, parallel-group, randomized trial conducted at 8 U.S. centers between February 2010 and December 2013. PARTICIPANTS: Sedentary men and women aged 70 to 89 at baseline who wore a hip-fitted accelerometer 7 consecutive days at baseline and 6, 12, and 24 months after randomization (N=1,341). MEASUREMENTS: Participants were randomized to a physical activity (PA; n = 669) intervention that included aerobic, resistance, and flexibility training or to a health education (HE; n = 672) intervention that consisted of workshops on older adult health and light upper-extremity stretching. Accelerometer patterns were characterized as bouts of sedentary (¡100 counts/min; ¿= 1, ¿= 10, ¿= 30, ¿= 60 minute lengths) and activity (¿= 100 counts/min; ¿= 1, ¿= 2, ¿= 5, ¿= 10 minute lengths) time. Each participant was categorized as having 0, 1 to 3, or 4 or more cumulative hospital days before each accelerometer assessment. RESULTS: Hospitalization increased sedentary time similarly in both intervention groups (8 min/d for 1-3 cumulative hospital days and 16 min/d for ¿= 4 cumulative hospital days). Hospitalization was also associated with less physical activity time across all bouts of less than 10 minutes (¿= 1: -7 min/d for 1-3 cumulative hospital days, -16 min/d for ¿= 4 cumulative hospital days; ¿= 2: -5 min/d for 1-3 cumulative hospital days, -11 min/d for ¿= 4 cumulative hospital days; ¿= 5: -3 min/d for 1-3 cumulative hospital days, -4 min/d for ¿= 4 cumulative hospital days). There was no evidence of recovery to prehospitalization levels (time effect p ¿ .41). PA participants had less sedentary time in bouts of less than 30 minutes than HE participants (-8 to -10 min/d) and more total activity (+3 to +6 min/d), although hospital-related changes were similar between the intervention groups (interaction effect p ¿ .26). CONCLUSION: Participating in a PA intervention before hospitalization had expected benefits, but participants remained susceptible to hospitalization's detrimental effects on their daily activity levels. There was no evidence of better activity recovery after hospitalization.
15 citations (Crossref) [2023-10-31] tex.eissn: 1532-5415 tex.orcid-numbers: Buford, Thomas W/0000-0002-9541-4358 Newton, Robert/0000-0002-6863-913X Wanigatunga, Amal/0000-0002-5763-5184 Gill, Thomas/0000-0002-6450-0368 Glynn, Nancy/0000-0003-2265-0162 tex.researcherid-numbers: Buford, Thomas W/B-1111-2011 tex.unique-id: ISI:000459714900011
Keywords: accelerometer; clinical trial; dept.hms; exercise; hospital; peer-reviewed; sedentary behavior

Changes in Lower Body Muscular Performance Following a Season of NCAA Division I Men’s Lacrosse - Talpey, Scott W.; Axtell, Robert; Gardner, Elizabeth; James, Lachlan (Sports, 2019)
The tactical and technical components of training become a primary emphasis, leaving less time for targeted development of physical qualities that underpin performance during the competition phase of a training program. A deemphasis on physical preparation during the in-season training phase may make athletes more susceptible to injury and decrease performance on the field. Two weeks prior to the start and one week following the conclusion of the 16-week collegiate lacrosse season, lower body force production was assessed in eight National Collegiate Athletic Association (NCAA) Division I Men’s Lacrosse athletes. Lower body force production capabilities were determined via the performance of countermovement jumps (CMJ) and drop jumps (DJ) performed on a force plate and isokinetic strength testing of the quadriceps and hamstring muscle groups across three velocities. Isokinetic strength of the hamstrings and the hamstring to quadriceps strength ratio were maintained or increased over the course of the competition phase of training. Relative peak force obtained from the CMJ and the reactive strength index from the DJ decreased significantly over the season. The maintenance of isokinetic strength and the decrease in CMJ and DJ performance may indicate the presence of neuromuscular fatigue that accumulated over the course of the season.
5 citations (Crossref) [2023-10-31] Number: 1
Keywords: Isokinetic; Power; Reactive strength; Strength; dept.hms; isokinetic; peer-reviewed; power; reactive strength; strength

Bullying perpetration and victimization among adolescents with overweight and obesity in a nationally representative sample - Rupp, Kristie; McCoy, Stephanie M. (Childhood Obesity, 2019)
19 citations (Crossref) [2023-10-31]
Keywords: dept.hms; peer-reviewed

A case for promoting movement medicine: preventing disability in the LIFE randomized controlled trial - Fanning, Jason; Rejeski, W Jack; Chen, Shyhhuei; Nicklas, Barbara J; Walkup, Michael P; Axtell, Robert S; Fielding, Roger A; Glynn, Nancy W; King, Abby C; Manini, Todd M; Mcdermott, Mary Mcgrae; Newman, Anne B; et al. (Journals of Gerontology Series A-biological Sciences and Medical Sciences, 2019)
Background: The movement profile of older adults with compromised function is unknown, as is the relationship between these profiles and the development of major mobility disability (MMD)-a critical clinical outcome. We first describe the dimensions of movement in older adults with compromised function and then examine whether these dimensions predict the onset of MMD. Methods: Older adults at risk for MMD (N = 1,022, mean age = 78.7 years) were randomized to receive a structured physical activity intervention or health education control. We assessed MMD in 6-month intervals (average follow-up of 2.2 years until incident MMD), with activity assessed at baseline, 6-, 12- and 24-month follow-up via accelerometry. Results: A principal components analysis of 11 accelerometer-derived metrics yielded three components representing lifestyle movement (LM), extended bouts of moderate-to-vigorous physical activity (MVPA), and stationary body posture. LM accounted for the greatest proportion of variance in movement (53%). Within health education, both baseline LM (HR = 0.74; 95% CI 0.62 to 0.88) and moderate-to-vigorous physical activity (HR = 0.69; 95% CI 0.54 to 0.87) were associated with MMD, whereas only LM was associated with MMD within physical activity (HR = 0.74; 95% CI 0.61 to 0.89). There were similar nonlinear relationships present for LM in both physical activity and health education (p ¡ .04), whereby risk for MMD was lower among individuals with higher levels of LM. Conclusions: Both LM and moderate-to-vigorous physical activity should be central in treatment regimens for older adults at risk for MMD.
8 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000491242600017, lens.org/077-007-606-131-474 tex.type: [object Object]
Keywords: Acceleration; Accelerometry; Age Factors; Aged; Aged; 80 and over; Aging; Confidence Intervals; Disability; Disability Evaluation; Exercise; Female; Geriatric Assessment; Humans; Linear Models; Male; Mobility Limitation; Physical Fitness; Physical activity; Prognosis; Sedentary; Sex Factors; Single-Blind Method; Walking Speed; acceleration; age; aged; aging; clinical trial; confidence interval; controlled study; dept.hms; disability; female; fitness; geriatric assessment; human; male; multicenter study; peer-reviewed; physiology; procedures; prognosis; randomized controlled trial; sex factor; single blind procedure; statistical model; very elderly; walking difficulty; walking speed

Spontaneous baroreflex sensitivity in normotensive African-American men - Latchman, Peter L.; Gates, Gregory J.; Thiel, Robert; Axtell, Robert S.; Zhu, Weili; Morin-Viall, Ally; Yue, Tianhong; Yang, Qin; Gardner, Kenneth; Meersman, Ronald E. De (Open Journal of Molecular and Integrative Physiology, 2019)
0 citations (Crossref) [2023-10-31]
Keywords: dept.hms; peer-reviewed

Flourishing and academic engagement among adolescents with overweight and obesity - Rupp, Kristie; McCoy, Stephanie M. (International Journal of Adolescent Medicine and Health, 2018)
Abstract Background Overweight and obesity in adolescence are associated with several negative health indicators; the association with flourishing, an indicator of overall well-being, is less clear. Objectives To examine associations between weight status and indicators of flourishing and academic engagement in adolescents. Subjects Analyses included 22,078 adolescents (10–17 years) from the 2016 National Survey of Children’s Health. Methods Adolescents were grouped according to body mass index (BMI) classification; outcomes included indicators of flourishing and academic engagement. Logistic regression models assessed the odds of each outcome comparing adolescents with overweight and adolescents with obesity to healthy weight adolescents. Results For flourishing, adolescents with overweight and adolescents with obesity were less likely to stay calm during a challenge (17% and 30%, respectively; p < 0.01); adolescents with obesity were 30% less likely to finish a task they started (p < 0.001), and 34% less likely to show interest in new things (p < 0.001) in comparison to healthy weight peers. Adolescents with obesity were 26% less likely to care about doing well in school (p < 0.001), and adolescents with overweight and adolescents with obesity were significantly less likely to complete all required homework (19% and 34%, respectively) (p < 0.001), in comparison to healthy weight peers. Conclusions A comprehensive approach to addressing overweight and obesity in adolescence should target improving academic engagement and flourishing to promote overall well-being.
3 citations (Crossref) [2023-10-31]
Keywords: academics; adolescence; dept.hms; dept.pch; flourishing; obesity; peer-reviewed

The effects of a carbon fiber shoe insole on athletic performance in collegiate athletes - Gregory, Robert W.; Axtell, Robert S.; Robertson, Marc I.; Lunn, William R. (Journal of Sports Science, 2018)
0 citations (Crossref) [2023-10-31]
Keywords: dept.hms; peer-reviewed

Evaluating accelerometry thresholds for detecting changes in levels of moderate physical activity and resulting major mobility disability - Rejeski, W. Jack; Walkup, Michael P.; Fielding, Roger A.; King, Abby C.; Manini, Todd M.; Marsh, Anthony P.; McDermott, Mary McGrae; Miller, Emily Y; Newman, Anne B.; Tudor-Locke, Catrine; Axtell, Robert S.; Miller, Michael E. (Journals of Gerontology Series A-biological Sciences and Medical Sciences, 2018)
Background: An important decision with accelerometry is the threshold in counts per minute (CPM) used to define moderate to vigorous physical activity (MVPA). We explore the ability of different thresholds to track changes in MVPA due to a physical activity (PA) intervention among older adults with compromised function: 760 CPM, 1,041 CPM, and an individualized threshold. We also evaluate the ability of change in accelerometry and self-reported PA to attenuate treatment effects on major mobility disability (MMD). Methods: Data from a week of hip worn accelerometers and self-reported PA data (30-day recall) were examined from baseline, 6-, 12-, and 24-months of follow-up on 1,528 older adults. Participants were randomized to either PA or Health Education (HE). MMD was objectively defined by loss of ability to walk 400 m during the follow-up. Results: The three thresholds yielded similar and higher levels of MVPA for PA than HE (p ¡ .001), however, this difference was significantly attenuated in participants with lower levels of physical function. Self-reported PA that captured both walking and strength training totally attenuated the intervention effect for MMD, an 18% reduction to a 3% increase. Accelerometer CPMs showed less attenuation of the intervention effect. Conclusions: Accelerometry assessment within the LIFE study was not sensitive to change in level in physical activity for older adults with very low levels of physical function. A combination of self-report and objective measures are recommended for use in physical activity intervention studies of the elderly; limitations of accelerometry deserve closer attention.
6 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000430696300014 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: Accelerometry; Aged; Aged; 80 and over; Female; Geriatric Assessment; Humans; LIFE-study; Male; Mobility Disability; Mobility Limitation; Motor Activity; Older Adults; Thresholds; Walking; accelerometry; aged; clinical trial; controlled study; dept.hms; female; geriatric assessment; human; male; motor activity; multicenter study; peer-reviewed; physiology; procedures; randomized controlled trial; very elderly; walking; walking difficulty

Rating of perceived exertion is a stable and appropriate measure of workload in judo. - Bromley, Sally J; Drew, Michael K; McIntosh, Andrew; Talpey, Scott (Journal of Science and Medicine in Sport, 2018)
OBJECTIVES: Heart rate (HR), blood lactate concentration [La] and/or rating of perceived exertion (RPE) have been utilised to monitor judo training load in technical and randori (competition training) sessions, but are yet to be investigated in mixed sessions containing both elements. Therefore the purpose of this study was to: (1) determine the stability of these variables, and (2) to assess the efficacy of RPE as a load variable for mixed judo sessions., DESIGN: Cross-sectional study., METHODS: Twenty-nine athletes attended two mixed training sessions at an international training camp. Bout and session characteristics, including RPE, physical and mental effort, heart rate (HR) and post-session [La] were recorded. A two-way random-effects intra-class correlation assessed variable stability. Multilevel mixed-effects ordered logistic regression investigated relationships between RPE and other variables for bouts and sessions., RESULTS: Average and minimum HR across sessions correlated highly (ICC=0.95 and 0.94, respectively). Good correlations existed between [La], session-RPE and mental effort, and fair correlation of max HR and physical effort. No relationships existed between [La]/HR and session-RPE. A unit increase in bout-RPE resulted in a 2.09 unit increase in physical, or a 1.36 unit increase in mental, effort holding all other bout variables constant. Gender and competitive level did not influence statistical models., CONCLUSIONS: Results provide further evidence that RPE can be used across a range of competitive levels and genders to monitor workload of mixed sessions and individual randori in judo. Physical effort may play a larger role than mental effort when athletes reflect on exertion during training. Copyright © 2018. Published by Elsevier Ltd.
4 citations (Crossref) [2023-10-31] Place: Australia Bromley, Sally J. Australian Institute of Sport, Australia; Australian Centre for Research into Injury in Sport and its Prevention (ACRISP), Federation University Australia, Australia. Electronic address: sally.bromley@ausport.gov.au. Drew, Michael K. Australian Institute of Sport, Australia; Australian Centre for Research into Injury in Sport and its Prevention (ACRISP), Federation University Australia, Australia. McIntosh, Andrew. Australian Centre for Research into Injury in Sport and its Prevention (ACRISP), Federation University Australia, Australia. Talpey, Scott. Australian Centre for Research into Injury in Sport and its Prevention (ACRISP), Federation University Australia, Australia; Exercise Science Department, Southern Connecticut State University, United States.
Keywords: *Martial Arts/ph [Physiology]; *Physical Exertion; *Workload; Adolescent; Adult; Athletes; Athletic performance; Combat sport; Cross-Sectional Studies; Epidemiological monitoring; Female; Heart Rate; Humans; Judo; Lactic Acid; Lactic Acid/bl [Blood]; Male; Martial Arts; Martial arts; Physical Exertion; Training load; Workload; Young Adult; adolescent; adult; article; athlete; athletic performance; blood; comparative effectiveness; cross-sectional study; dept.hms; drug efficacy; epidemiological monitoring; exercise; female; gender; heart rate; human; human experiment; human tissue; judo; lactic acid; male; martial art; peer-reviewed; physiology; workload; young adult

Muscle strength assessment - Axtell, Robert S. (ACSM's Exercise Testing and Prescription, 2018)
ACSM’S Exercise Testing and Prescription adapts and expands upon the assessment and exercise prescription-related content from ACSM’s Resource Manual for Guidelines for Exercise Testing and Prescription, 7th Edition, to create a true classroom resource. Fully aligned with the latest edition of ACSM’s flagship title, ACSM’s Guidelines for Exercise Testing and Prescription , this practical resource walks students through the process of selecting and administering fitness assessments, using Guidelines to interpret results, and drafting an exercise prescription that is in line with Guidelines parameters .Designed for today’s learners, the text is written in a clear, concise style, and enriched by visuals that promote student engagement. As an American College of Sports Medicine publication, the book offers the unsurpassed quality and excellence that has become synonymous with titles by the leading exercise science organization in the world.The nuances of fitness assessment and the particulars of crafting exercise prescriptions are explored in expansive sections throughout the book.A full section devoted to Special Populations prepares students to meet the needs of the full range of both typically healthy and special needs clients they’ll see in practice.Comprehensive case studies written by experts to reinforce practical applications of concepts.A wide range of online resources includes laboratory materials and activities that provide opportunities for hands-on learning, and a library of journal articles that helps students connect research to practice.100% alignment with the most up-to-date version of the ACSM’s Guidelines for Exercise Testing and Prescription enhances the learning experience, making it easy to go back and forth between Guidelines and the text.eBook available. Fast, smart, and convenient, today’s eBooks can transform learning. These interactive, fully searchable tools offer 24/7 access on multiple devices, the ability to highlight and share notes, and much more.
Keywords: dept.hms

Special considerations for the lifespan: Elderly population - Robertson, M.I.; Axtell, Robert (ACSM's Exercise Testing and Prescription, 2018)
ACSM’S Exercise Testing and Prescription adapts and expands upon the assessment and exercise prescription-related content from ACSM’s Resource Manual for Guidelines for Exercise Testing and Prescription, 7th Edition, to create a true classroom resource. Fully aligned with the latest edition of ACSM’s flagship title, ACSM’s Guidelines for Exercise Testing and Prescription , this practical resource walks students through the process of selecting and administering fitness assessments, using Guidelines to interpret results, and drafting an exercise prescription that is in line with Guidelines parameters .Designed for today’s learners, the text is written in a clear, concise style, and enriched by visuals that promote student engagement. As an American College of Sports Medicine publication, the book offers the unsurpassed quality and excellence that has become synonymous with titles by the leading exercise science organization in the world.The nuances of fitness assessment and the particulars of crafting exercise prescriptions are explored in expansive sections throughout the book.A full section devoted to Special Populations prepares students to meet the needs of the full range of both typically healthy and special needs clients they’ll see in practice.Comprehensive case studies written by experts to reinforce practical applications of concepts.A wide range of online resources includes laboratory materials and activities that provide opportunities for hands-on learning, and a library of journal articles that helps students connect research to practice.100% alignment with the most up-to-date version of the ACSM’s Guidelines for Exercise Testing and Prescription enhances the learning experience, making it easy to go back and forth between Guidelines and the text.eBook available. Fast, smart, and convenient, today’s eBooks can transform learning. These interactive, fully searchable tools offer 24/7 access on multiple devices, the ability to highlight and share notes, and much more.
Keywords: dept.hms

Effect of age on dynamic walking balance in a healthy population between the ages of 20 and 80 years - Robertson, Marc; Gregory, Robert (Physical Therapy and Rehabilitation, 2018)
2 citations (Crossref) [2023-10-31] Citation Key Alias: robertsonEffectAgeDynamic2018a
Keywords: dept.hms; peer-reviewed

Solving the acoustic issue in physical education settings - Ryan, Stu; Swartz, Daniel R (International Journal of Physical Education, Fitness and Sports, 2018)
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/079-502-562-751-84X tex.type: [object Object]
Keywords: dept.hms; peer-reviewed

Bright 1 bodies: extending the bright bodies family-based intensive lifestyles therapy to adolescents with type 1 diabetes - Ash, Garrett I; Joiner, Kevin L; Savoye, Mary; Baker, Julien S; Gerosa, James; Kleck, Emma; Patel, Neha S; Stultskolehmainen, Matthew A; Weinzimer, Stuart A; Grey, Margaret (Annals of Behavioral Medicine, 2018)
5 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/134-102-073-475-880 tex.type: [object Object]
Keywords: dept.hms; peer-reviewed

Safety and health outcomes of a physical activity program for adolescents with Type 1 Diabetes - Ash, Garrett I; Joiner, Kevin L; Savoye, Mary; Baker, Julien S; Gerosa, James; Kleck, Emma; Patel, Neha S; Stultskolehmainen, Matthew A; Weinzimer, Stuart A; Grey, Margaret (ACSM's 65th Annual Meeting, 2018)
Citation Key Alias: lens.org/149-915-175-995-302
Keywords: dept.hms; ⛔ No DOI found

The status of physical activity opportunities in Idaho schools. - Berei, Catherine P; Karp, Grace Goc; Kauffman, Katie (The Physical Educator, 2018)
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/104-344-030-444-113 tex.type: [object Object]
Keywords: dept.hms

Dose of physical activity, physical functioning and disability risk in mobility-limited older adults: Results from the LIFE study randomized trial. - Fielding, Roger A; Guralnik, Jack M; King, Abby C; Pahor, Marco; McDermott, Mary M; Tudor-Locke, Catrine; Manini, Todd M; Glynn, Nancy W; Marsh, Anthony P; Axtell, Robert S; Hsu, Fang-Chi; Rejeski, W Jack; et al. (PLoS ONE, 2017)
Understanding the minimal dose of physical activity required to achieve improvement in physical functioning and reductions in disability risk is necessary to inform public health recommendations. To examine the effect of physical activity dose on changes in physical functioning and the onset of major mobility disability in The Lifestyle Interventions and Independence for Elders (LIFE) Study. We conducted a multicenter single masked randomized controlled trial that enrolled participants in 2010 and 2011 and followed them for an average of 2.6 years. 1,635 sedentary men and women aged 70-89 years who had functional limitations were randomized to a structured moderate intensity walking, resistance, and flexibility physical activity program or a health education program. Physical activity dose was assessed by 7-day accelerometry and self-report at baseline and 24 months. Outcomes included the 400 m walk gait speed, the Short Physical Performance Battery (SPPB), assessed at baseline, 6, 12, and 24 months, and onset of major mobility disability (objectively defined by loss of ability to walk 400 m in 15 min). When the physical activity arm or the entire sample were stratified by change in physical activity from baseline to 24 months, there was a dose-dependent increase in the change in gait speed and SPPB from baseline at 6, 12, and 24 months. In addition, the magnitude of change in physical activity over 24 months was related to the reduction in the onset of major mobility disability (overall P < 0.001) (highest versus the lowest quartile of physical activity change HR 0.23 ((95% CI:0.10-0.52) P = 0.001) in the physical activity arm. We observed a dose-dependent effect of objectively monitored physical activity on physical functioning and onset of major mobility disability. Relatively small increases (> 48 minutes per week) in regular physical activity participation had significant and clinically meaningful effects on these outcomes., TRIAL REGISTRATION: ClinicalsTrials.gov NCT00116194.
89 citations (Crossref) [2023-10-31] Place: United States Fielding, Roger A. Nutrition, Exercise Physiology, and Sarcopenia Laboratory, Jean Mayer USDA Human Nutrition Research Center on Aging at Tufts University, Boston, MA, United States of America. Guralnik, Jack M. Department of Epidemiology and Public Health, University of Maryland School of Medicine, 4655 W. Baltimore Street, Baltimore, MD, United States of America. King, Abby C. Department of Health Research & Policy, and Stanford Prevention Research Center, Department of Medicine, Stanford University Medical School, Stanford, CA, United States of America. Pahor, Marco. Department of Aging and Geriatric Research, University of Florida College of Medicine, Gainesville, FL, United States of America. McDermott, Mary M. Department of Medicine, Northwestern University Feinberg School of Medicine, 750 N Lake Shore Drive, 10th Floor, Chicago, IL, United States of America. Tudor-Locke, Catrine. Department of Kinesiology, University of Massachusetts Amherst, Amherst, MA, United States of America. Tudor-Locke, Catrine. Pennington Biomedical Research Center, Louisiana State University System, Baton Rouge, LA, United States of America. Manini, Todd M. Department of Aging and Geriatric Research, University of Florida College of Medicine, Gainesville, FL, United States of America. Glynn, Nancy W. Center for Aging and Population Health, Department of Epidemiology, Graduate School of Public Health, University of Pittsburgh, Pittsburgh, PA, United States of America. Marsh, Anthony P. Department of Health and Exercise Science, Wake Forest University, Winston-Salem, NC, United States of America. Axtell, Robert S. Department of Exercise Science, Southern Connecticut State University, New Haven, CT. Hsu, Fang-Chi. Department of Biostatistical Sciences, Division of Public Health Sciences, Wake Forest School of Medicine, Winston-Salem, NC, United States of America. Rejeski, W Jack. Center for Aging and Population Health, Department of Epidemiology, Graduate School of Public Health, University of Pittsburgh, Pittsburgh, PA, United States of America.
Keywords: *Activities of Daily Living; *Disabled Persons; *Exercise; *Mobility Limitation; Activities of Daily Living; Aged; Aged; 80 and over; Article; Disabled Persons; Exercise; Female; Humans; Male; Mobility Limitation; accelerometry; aged; controlled study; daily life activity; dept.hms; disabled person; education program; exercise; exercise intensity; female; human; incidence; major clinical study; male; multicenter study; outcome assessment; peer-reviewed; physical activity; physical activity; capacity and performance; physical disability; physical functioning; physical mobility; physical performance; randomized controlled trial; resistance training; risk assessment; risk factor; sedentary lifestyle; self report; very elderly; walking difficulty; walking speed

Device-measured physical activity as a predictor of disability in mobility-limited older adults - Mankowski, Robert T.; Anton, Stephen D.; Axtell, Robert; Chen, Shyh-Huei; Fielding, Roger A.; Glynn, Nancy W.; Hsu, Fang-Chi; King, Abby C.; Layne, Andrew S.; Leeuwenburgh, Christiaan; Manini, Todd M.; Marsh, Anthony P.; et al. (Journal of the American Geriatrics Society, 2017)
OBJECTIVES: To examine associations between objectively measured physical activity (PA) and incidence of major mobility disability (MMD) and persistent MMD (PMMD) in older adults in the Lifestyle Interventions and Independence for Elders (LIFE) Study. DESIGN: Prospective cohort of individuals aged 65 and older undergoing structured PA intervention or health education. SETTING: The LIFE Study was a multicenter (eight sites) randomized controlled trial designed to compare the efficacy of a long-term structured PA intervention with that of a health education (HE) program in reducing the incidence of MMD in mobility-limited older adults. PARTICIPANTS: LIFE Study participants (n = 1,590) had a mean age +/- standard deviation of 78.9 +/- 5.2, low levels of PA, and measured mobility-relevant functional impairment at baseline. MEASUREMENTS: Activity data were collected using hip-worn 7-day accelerometers at baseline and 6, 12, and 24 months after randomization to test for associations with incident MMD and PMMD (¿= 2 consecutive instances of MMD). RESULTS: At baseline, every 30 minutes spent being sedentary (¡100 accelerometry counts per minute) was associated with higher rate of subsequent MMD (10%) and PMMD (11%) events. Every 500 steps taken was associated with lower rate of MMD (15%) and PMMD (18%). Similar associations were observed when fitting accelerometry-based PA as a time-dependent variable. CONCLUSION: Accelerometry-based PA levels were strongly associated with MMD and PMMD events in older adults with limited mobility. These results support the importance of daily PA and lower amounts of sedentary time levels in this population and suggest that accelerometry may be a useful tool for assessing risk of mobility disability.
25 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000417650000023, lens.org/040-976-851-672-995 tex.eissn: [object Object] tex.orcid-numbers: [object Object] tex.researcherid-numbers: [object Object] tex.unique-id: [object Object]
Keywords: Accelerometry; Aged; Aged; 80 and over; Article; Disability Evaluation; Exercise; Female; Geriatric Assessment; Humans; Male; Mini Mental State Examination; Mobility Limitation; Physical Therapy Modalities; Pittsburgh Sleep Quality Index; Sedentary Lifestyle; Time Factors; accelerometry; aged; clinical trial; cohort analysis; controlled study; depression; dept.hms; disability; educational status; ethnic group; exercise; female; functional disease; geriatric assessment; health education; human; major clinical study; major mobility disability; male; marriage; mobility disability; multicenter study; older adults; peer-reviewed; persistent major mobility disability; physical activity; physiotherapy; procedures; prospective study; randomized controlled trial; sedentary lifestyle; sedentary time; sleep quality; time factor; very elderly; walking difficulty

Effects of a Long-Term Physical Activity Program on Activity Patterns in Older Adults. - Wanigatunga, Amal A; Tudor-Locke, Catrine; Axtell, Robert S; Glynn, Nancy W; King, Abby C; McDermott, Mary M; Fielding, Roger A; Lu, Xiaomin; Pahor, Marco; Manini, Todd M (Medicine and science in sports and exercise, 2017)
PURPOSE: To examine the effect of a long-term structured physical activity (PA) intervention on accelerometer-derived metrics of activity pattern changes in mobility-impaired older adults., METHODS: Participants were randomized to either a PA or health education (HE) program. The PA intervention included a walking regimen with strength, flexibility, and balance training. The HE program featured health-related discussions and a brief upper body stretching routine. Participants (n = 1341) wore a hip-worn accelerometer for >=10 h.d for >=3 d at baseline and again at 6, 12, and 24 months postrandomization. Total PA (TPA)-defined as movements registering 100+ counts per minute-was segmented into the following intensities: low-light PA (LLPA; 100-759 counts per minute), high light PA (HLPA; 760-1040 counts per minute), low moderate PA (LMPA; 1041-2019 counts per minute), and high moderate and greater PA (HMPA; 2020+ counts per minute). Patterns of activity were characterized as bouts (defined as the consecutive minutes within an intensity)., RESULTS: Across groups, TPA decreased an average of 74 min.wk annually. The PA intervention attenuated this effect (PA = -68 vs HE: -112 min.wk, P = 0.002). This attenuation shifted TPA composition by increasing time in LLPA (10+ bouts increased 6 min.wk), HLPA (1+, 2+, 5+, and 10+ bouts increased 6, 3, 2, and 1 min.wk, respectively), LMPA (1+, 2+, 5+, and 10+ bouts increased: 19, 17,16, and 8 min.wk, respectively), and HMPA (1+, 2+, 5+, and 10+ bouts increased 23, 21, 17, and 14 min.wk, respectively)., CONCLUSIONS: The PA intervention increased PA by shifting the composition of activity toward higher-intensity activity in longer-duration bouts. However, a long-term structured PA intervention did not completely eliminate overall declines in total daily activity experienced by mobility-impaired older adults.
26 citations (Crossref) [2023-10-31] Place: United States Wanigatunga, Amal A. 1Department of Epidemiology, Johns Hopkins University, Baltimore, MD; 2Department of Kinesiology, University of Massachusetts Amherst, Amherst, MA; 3Exercise Science Department, Southern Connecticut State University, New Haven, CT; 4Department of Epidemiology, University of Pittsburgh, Pittsburgh, PA; 5Department of Health Research and Policy and Department of Medicine, Stanford University, School of Medicine, Stanford, CA; 6Feinberg School of Medicine, Northwestern University, Evanston, IL; 7Nutrition, Exercise Physiology and Sarcopenia Laboratory, Jean Mayer United States Department of Agriculture Human Nutrition Research Center on Aging, Tufts University, Boston, MA; 8Department of Biostatistics, University of Florida, Gainesville, FL; and 9Department of Aging and Geriatric Research, University of Florida, Gainesville, FL.
Keywords: *Aged/ph [Physiology]; *Exercise; *Health Promotion; ACCELEROMETER; ACTIVITY BOUTS; Accelerometry; Age Factors; Aged; Aged; 80 and over; ELDERLY; Exercise; Female; Health Promotion; Humans; LIGHT-INTENSITY PHYSICAL ACTIVITY; Male; Mobility Limitation; PHYSICAL ACTIVITY INTERVENTION; Program Evaluation; Sedentary Behavior; Sedentary Lifestyle; accelerometry; age; aged; clinical trial; controlled study; dept.hms; exercise; female; health promotion; human; male; multicenter study; peer-reviewed; physiology; program evaluation; randomized controlled trial; sedentary lifestyle; very elderly; walking difficulty

Household support for physical activity in adolescent girls recruited from lower SES neighborhoods - Rupp, Kristie; Taverno Ross, Sharon E.; Gary-Webb, Tiffany L.; Akiva, Thomas; Jakicic, John M. (Medicine & Science in Sports & Exercise, 2017)
0 citations (Crossref) [2023-10-31]
Keywords: dept.hms

Perceptions of PEP grant influences on CSPAP implementation - Berei, Catherine P.; Karp, Grace Goc; Olsen, Simon; Fennell, Marcis; Drake, Elisa (Research Quarterly for Exercise and Sport, 2017)
tex.eissn: 2168-3824 tex.unique-id: ISI:000401115400154
Keywords: dept.hms; peer-reviewed; ⛔ No DOI found

Guideposts and roadblocks to the career-long scholarly engagement of physical education teacher education faculty - Berei, Catherine P; Pratt, Erica; Parker, Melissa; Shephard, Kevin; Liang, Tanjian; Nampai, Udon; Neamphoka, Guntima (Research Quarterly for Exercise and Sport, 2017)
Purpose: Scholarship is essential for the growth and development of the physical education field. Over time, scholarship expectations have changed, forcing faculty members to alter time spent for research, teaching, and service. Social-cognitive career theory (SCCT) presents a model for understanding performance and persistence in an occupational environment. The interconnected aspects of SCCT have different emphasis related to self-efficacy, outcome expectations, or personal goals pursuit. This study explored physical education teacher education (PETE) faculty members' continuing engagement in scholarly activity through SCCT. Method: Data collection included interviews with 9 senior PETE faculty members who met the criteria for “productive scholars over time.” Curriculum vitae were collected to verify productivity. Results: Data analysis revealed guidepost themes that included collaborating, finding balance, defining a research process, and maintaining a strong work ethic. Roadblocks encountered included other obligations and lack of support for research. Conclusions: Participants demonstrated strong self-efficacy; held high, positive expectations for success; and set very specific, clear, and deliberate goals. Participant behavior was moderated by their personal attributes (capacity to build relationships, set goals, and maintain interest and passion) and was tempered by the environments in which they worked. Fostering similar behaviors has the potential to guide future and current PETE faculty members in creating supportive and encouraging atmospheres for sustained productivity. The lack of literature relating to this topic warrants the need for more research exploring the influential factors and benefits gained from sustained scholarly productivity over time for PETE faculty members.
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/072-589-102-475-389 tex.type: [object Object]
Keywords: Academic publishing; Ethics; Professional; Female; Goals; Humans; Male; Physical Education and Training; Research; School Teachers; Self Efficacy; adult; atmosphere; barriers to productivity; career; curriculum; data analysis; dept.hms; expectation; faculty research productivity; female; higher education research; human; human experiment; interview; male; medical ethics; motivation; peer-reviewed; physical education; productivity; psychology; publishing; research; school teacher; self concept; teacher training; theoretical study

Integrating CSPAP into the PETE programs at Southern Connecticut State University and Central Connecticut State University - Ciotto, Carol M; Fede, Marybeth H (The Journal of Physical Education, Recreation & Dance, 2017)
6 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/080-884-940-096-419 tex.type: [object Object]
Keywords: dept.hms

Cultivating leadership, pedagogy and programming for CSPAP and healthy, active lifestyles at the University of Idaho. - Karp, Grace Goc; Brown, Helen; Scruggs, Philip W; Berei, Catherine P (The Journal of Physical Education, Recreation & Dance, 2017)
8 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/038-401-000-460-370 tex.type: [object Object]
Keywords: dept.hms

Cardiovagal tone: A predictor of heart rate adjusted augmentation index in men but not in women - Latchman, Peter L.; Thiel, Robert; Gates, Gregory; Zhu, Weili; Axtell, Robert; Gardner, Kenneth; Lunn, William; DeMeersman, Ronald (Open Journal of Molecular and Integrative Physiology, 2017)
2 citations (Crossref) [2023-10-31]
Keywords: dept.hms; peer-reviewed

Concurrent validation of the tandem walk test as a measure of dynamic walking balance in a healthy population - Robertson, Marc; Gregory, Robert (Physical Therapy and Rehabilitation, 2017)
4 citations (Crossref) [2023-10-31] Citation Key Alias: robertsonConcurrentValidationTandem2017a
Keywords: dept.hms; peer-reviewed